Peran Komunikasi Guru dalam Membangun Kecerdasan Emosional Anak Penyandang Autisme di SKH YKDW 01 Tangerang - Samarsya, Rinda; Een Irianti; Rahayu, Riza Gusti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study examines the role of teacher communication in building the emotional intelligence of children with autism at SKh YKDW 01 Tangerang. The primary focus is to understand how effective communication can help children with autism develop their emotional and social skills. The research method used is a qualitative approach with techniques such as observation, in-depth interviews, and documentation. The results show that children with autism have limitations in communication. Teachers at SKh YKDW 01 Tangerang implement a communication approach that is simple, firm, and consistent, and collaborate with parents to ensure that messages received by the child are consistent across different environments. Strategies such as giving one-word instructions, using non-verbal cues, and creating a structured and supportive learning environment have proven effective in helping autistic children understand and respond to instructions better. This study highlights the importance of a deep understanding of the individual characteristics of each autistic child and the need for tailored communication strategies to support their emotional and social development